PREMATURE CORONARY HEART DISEASE IN A YOUNG ADULT- PERNICIOUS ANEMIA THE UNDERLYING CULPRIT: A CASE REPORT: Premature Coronary Heart Disease - Burney, Shamaila; Ahmed, Saqib Qayyum; Zafar, Saerah Iffat (Pakistan Armed Forces Medical Journal, 2015)
IntroductionMegaloblastic anemia is frequently seen in Pakistan with vitamin B12 deficiency as a leading cause. However prevalence of pernicious anemia is low in our population. Vitamin B12 deficiency can result in elevated homocysteine levels which is associated with atherothrombotic diseases and pernicious anemia can be a cause as reported in recent studies.